Clinical application of autologous technetium-99m-labelled eosinophils to detect focal eosinophilic inflammation in the lung. Issue 11 (24th June 2015) - Loutsios, Chrystalla; Farahi, Neda; Simmonds, Rosalind; Cullum, Ian; Gillett, Daniel; Solanki, Chandra; Solanki, Kishor; Buscombe, John; Condliffe, Alison M; Peters, A Mike; Chilvers, Edwin R
Abstract : Abstract: The detection of focal eosinophilic inflammation by non-invasive means may aid the diagnosis and follow-up of a variety of pulmonary pathologies. All current methods of detection involve invasive sampling, which may be contraindicated or too high-risk to be performed safely. The use of injected autologous technetium-99m (Tc-99m)-labelled eosinophils coupled to single-photon emission computed tomography (SPECT) has been demonstrated to localise eosinophilic inflammation in the lungs of a patient with antineutrophil cytoplasmic antibody-positive vasculitis. Here, we report on the utility of this technique to detect active eosinophilic inflammation in a patient with focal lung inflammation where a biopsy was contraindicated.